2020
DOI: 10.1088/1755-1315/484/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic relationship and heritability among F2 generation of four crosses in rice using agro-morphological markers

Abstract: Due to its higher consumption in Asian populations, white rice may lead to increase risk of developing type 2 diabetes mellitus. The glycaemic index of rice renders it the main contributor to dietary glycaemic load. Even though there are abundant rice genetic resources, the incorporation of germplasm sources is very important when looking for new alleles that play a role to prevention of the type 2 diabetes mellitus. Four rice cultivars were crossed to obtain low glycaemic index genotype in our previous resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The distribution of lipid and glucose levels and body composition profile data for all subjects are shown in figure 2. Body composition was not correlated with insulin resistance using the HOMA-IR index, in line with a previous study (Lisnawati et al, 2023). The difference in the index parameters used was also a cause.…”
Section: Resultssupporting
confidence: 89%
“…The distribution of lipid and glucose levels and body composition profile data for all subjects are shown in figure 2. Body composition was not correlated with insulin resistance using the HOMA-IR index, in line with a previous study (Lisnawati et al, 2023). The difference in the index parameters used was also a cause.…”
Section: Resultssupporting
confidence: 89%
“…The results showed that the heritability values ranged between medium and high; the characters of maximum growth potential, germination ability, and germination time had moderate heritability values, while the dry weight of sprouts had high heritability values. The coefficient value of genetic diversity provides information about the variety of data resulting from a study; the high or low weight of the coefficient of gene diversity depends on the germination produced from several cultivars used; the higher the coefficient value of genetic diversity, the more diverse germinations are made and vice versa [16,17].…”
Section: Germinationmentioning
confidence: 99%
“…Rice (Oryza sativa L.), the most important dietary carbohydrate in the world, is a monocotyledonous angiosperm that belongs to the family Gramineae (Kumar et al 2020). Asian countries comprise almost 90% of both the world's rice producers and consumers (Kusmiyati et al 2020). In Bangladesh, food security is synonymous with rice security.…”
Section: Introductionmentioning
confidence: 99%